CHILDHOOD, LOOKS AND MOUNTS: EXPERIENCES AND RESEARCH WITH CHILDREN AND EDUCATION - Pereira Leite, Cesar Donizetti [UNESP]; Isler Pereira Leite, Adriana Regina; Christofoletti, Rafael [UNESP] (Univ Estadual Campinas, Fac Educacao, 2017)
This text is intended to work on three themes: cinema, the production of images of children, education and childhood. We will try to establish these relationships based on research work that we have developed with imagery production and elementary school children. We will work with some themes, from a perspective that will assume the idea of text-essay-film. The purpose is, as in the cinema, to present the text in the form of sinopse, argument, pre-production, production and post-production.The focus will be on the Time and Body issues that emerge in this study. Our reflection will be based on authors such as Deleuze, Foucault.
Keywords: Childhood; Cinema; Image; Education